2001
DOI: 10.1017/s0022029901004757
|View full text |Cite
|
Sign up to set email alerts
|

Thermal inactivation kinetics of bovine cathepsin D

Abstract: Cathepsin D, the principal indigenous acid proteinase in bovine milk, is a lysosomal proteinase, which exists in milk in four forms, including the inactive zymogen procathepsin D. The thermal inactivation kinetics of bovine cathepsin D, isolated from spleen and milk, were studied under isothermal conditions, using a specific HPLC assay to determine residual activity. Inactivation of the blood enzyme preparation followed first order kinetics, with z-values in phosphate buffer (pH 6·7) and skimmed milk of 6·5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…The role of the indigenous milk acid proteinase cathepsin D, which also degrades α s1 -casein to α s1 -I casein [23], should be considered, as it has recently been shown that it is relatively stable under high temperature cheese cooking conditions (~45% survival after heating at 55 o C for 30 min [13]). However, it is generally regarded that its relative contribution to cheese ripening is masked by the much higher activity of chymosin in curd, although no studies have directly compared the relative activities and extents of inactivation of the two enzymes during cheese manufacture, which makes direct interpretation of its contribution to the results shown, although potentially important, difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the indigenous milk acid proteinase cathepsin D, which also degrades α s1 -casein to α s1 -I casein [23], should be considered, as it has recently been shown that it is relatively stable under high temperature cheese cooking conditions (~45% survival after heating at 55 o C for 30 min [13]). However, it is generally regarded that its relative contribution to cheese ripening is masked by the much higher activity of chymosin in curd, although no studies have directly compared the relative activities and extents of inactivation of the two enzymes during cheese manufacture, which makes direct interpretation of its contribution to the results shown, although potentially important, difficult.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that during cooking at temperatures up to 55°C, the enzyme is partially and reversibly denatured and can be partially reactivated during ripening (Hayes et al 2002(Hayes et al , 2004. Moreover, according to Hayes et al (2001), residual chymosin activity in high-cooked cheeses may be partially attributed to cathepsin D, which is less heat-labile than chymosin and hydrolyses the assay substrate similarly to chymosin under the same conditions. However, no evidence was observed supporting this suggestion (Section 2.5).…”
Section: Residual Chymosin Activitymentioning
confidence: 99%
“…However, no evidence was observed supporting this suggestion (Section 2.5). Furthermore, the quantity of this enzyme in the cheese milk is low and its activity is mainly found in milk whey and not in the casein fraction (Hayes et al 2001).…”
Section: Residual Chymosin Activitymentioning
confidence: 99%
“…Cathepsin D has been shown to be relatively heatstable and to partially survive not only pasteurisation at 72 1C for 15 or 30 s , but also heating at 55 1C for 30 min, as used during manufacture of highcook cheese varieties (Hayes et al, 2001). Furthermore, 20% of the activity of a partially purified fraction of cysteine protease survived heat treatment at 72 1C for 30 s .…”
Section: Article In Pressmentioning
confidence: 99%